CYBER ATTACK DETECTION AND MONITORING SYSTEM FOR COMPUTER NETWORKS BASED ON ARTIFICIAL INTELLIGENCE - Uzoqov Farkhod G'afforovich (GLOBAL SCIENTIFIC RESEARCH AND INTELLECTUAL PURSUITS, 2025)
This article discusses the detection and countermeasures of cyber threats in modern computer networks. It discusses a system for detecting and monitoring network attacks based on artificial intelligence technologies.